Fluoroscopy as Definitive Postreduction Imaging of Pediatric Wrist and Forearm Fractures Is Safe and Saves Time. Issue 1 (January 2020) - Goodman, Avi D.; Walsh, Devin F.; Zonfrillo, Mark R.; Eberson, Craig P.; Cruz, Aristides I.
Abstract : Background: Recent studies indicate that formal postreduction radiographs may be unnecessary for closed, isolated pediatric wrist, and forearm when mini C-arm fluoroscopy is used for reduction. Our institution changed the Emergency Department (ED) management protocol to reflect this by allowing orthopaedic providers to determine if fluoroscopy was acceptable to assess fracture reduction. We hypothesized that using fluoroscopy as definitive postreduction imaging would decrease total encounter time, without an increase in the rate of rereduction or surgery. Methods: Patients with closed, isolated distal radius/distal ulna (DR/DU) or both bone forearm (BBFA) fractures that required sedation and reduction under mini C-arm fluoroscopy at our Level 1 pediatric ED were reviewed for 6 months both before and after this policy change. Before, all patients had formal postreduction radiographs; after, the decision was left to the orthopaedic physician. Timestamp data were collected, as was the need for rereduction or surgery. In addition to descriptive statistics, between-group differences were analyzed with the Student t test, χ 2 test, and multivariable regression as appropriate. Results: A total of 243 patients (119 before, 124 after) had 165 DR/DU and 78 BBFA fractures. Demographic data were similar before and after. After protocol implementation, univariable analysis (Student t test) showed that sedation times were longer, while total ED time and the time from sedation beginning to discharge were similar. The proportion of patients requiring rereduction or surgery were similar. After multivariable regression, "fluoroscopy as definitive imaging" was the only independent determinant of the time intervals compared with using conventional radiography. Sedation was an average of 13.8 minutes longer ( P <0.001), while the interval from sedation beginning to discharge was 15.8 minutes shorter ( P =0.007), and total ED time was 33.0 minutes shorter ( P =0.018). Fluoroscopy as definitive imaging was not a predictor of surgery (odds ratio=0.63, P =0.520), although having a BBFA increased the likelihood (odds ratio=4.50, P =0.008). Conclusions: Implementing a protocol in which the provider could use mini C-arm fluoroscopy for definitive postreduction imaging did not result in increased rates remanipulation or need for surgery. Regression analysis further demonstrated time savings associated with foregoing conventional radiographs. Level of Evidence: Level III—therapeutic.